Analisa Potensi Kota Batam Sebagai Pusat Pengembangan Industri Teknologi Informasi Dan Komunikasi - Ronny Juwono; Nona Mahditiara Aryuni Sumanang (President University, 2016)
Batam is known as one of big industrial city in Indonesia. It has many potential, both local and foreign, to support the industrial growth. However, the growth of industry in information and communication technology (ICT) is relatively slow. In 2008, the government stated that Batam is a Digital Island where ICT become the main focus industry. Nevertheless, only a few ICT industries have emerged and survived in current days. This research considered that the local government should implement good strategies as a comprehensive plan for the ICT long term development. In order to create the strategic plan, focus on the local potentials is essential. In this research, there were four potentials to support the development of ICT industry. The aim of this research was to find the top priority of those potentials. Survey was conducted using questionnaire and some interview to hardware industry, software industry, computer distributors, universities, training facilities, and local government institution. Analytic Hierarchical Process (AHP) was used to find the priority of the potentials. The result indicated that the demand for skilled workers was the top priority among the other potentials. Therefore, this should be considered as the main focus in ICT development plan.